The Bad Guys in Attack of the zittens - Blabey, Aaron (Blabey, Aaron. Bad guys., 2017)
When the world is threatened by a horde of zombie kittens, the Bad Guys enlist the help of Agent Fox, a swampy zombie antidote, and the hungriest granny around.